2017
DOI: 10.3892/etm.2017.4779
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-320 regulates autophagy in retinoblastoma by targeting hypoxia inducible factor-1α

Abstract: Abstract. Retinoblastoma (RB) is the most common malignancy in children. Due to refractory mechanisms of chemoresistance and the toxicity of chemotherapies, novel therapies for RB treatment are urgently required. MicroRNA-320 (miR-320) is believed to be associated with the tumorigenesis of RB, although the mechanism remains unclear. Considering the hypoxic intratumoral region, the roles of miR-320 and hypoxia inducible factor-1α (HIF-1α) in the regulation of autophagy were investigated in 30 human RB samples a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Among the five previously identified ARGs associated with MM, HIF1A is the most widely studied (59,60). Hypoxia, a central characteristic for cancer incidence and progression, occurs when most types of cancer are evolving (59)(60)(61)(62)(63)(64). HIF1A is a hypoxia-inducible factor, and constitutive expression of HIF1A in MM indicates that suppression of HIF1A-mediated transcription could become a favorable target for MM (65)(66)(67)(68).…”
Section: Discussionmentioning
confidence: 99%
“…Among the five previously identified ARGs associated with MM, HIF1A is the most widely studied (59,60). Hypoxia, a central characteristic for cancer incidence and progression, occurs when most types of cancer are evolving (59)(60)(61)(62)(63)(64). HIF1A is a hypoxia-inducible factor, and constitutive expression of HIF1A in MM indicates that suppression of HIF1A-mediated transcription could become a favorable target for MM (65)(66)(67)(68).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs may act as tumour suppressors or oncogenes, in which aberrantly downregulated miRNAs play tumour-suppressive roles, whereas highly expressed miRNAs serve oncogenic roles in carcinogenesis and cancer progression (12). Emerging studies have indicated that numerous miRNAs are dysregulated in RB, such as miR-29a (13), miR-320 (14), miR-613 (15) and miR-143 (16). Aberrantly expressed miRNAs are closely related with RB formation and progression by regulating various pathological behaviours, such as cellular proliferation, apoptosis, invasion, metastasis and angiogenesis (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…The role of adequate SIRT1 levels for proper liver function is well documented, as SIRT1 deletion results in hepatic steatosis and inflammation, and SIRT1 activators improve hepatosteatosis and insulin resistance [80,81]. MicroRNA-320 may also regulate the development of autophagy by targeting hypoxia-inducible factor-1α (HIF-1α) and mTOR under hypoxic conditions [82]. Dysregulation of the mTOR pathway-a key controller of lipid metabolism, regulating lipogenesis in the liver, lipolysis in white adipose tissue, and adipogenesis-may promote liver steatosis and development of NAFLD [83].…”
Section: Discussionmentioning
confidence: 99%